1987
DOI: 10.1145/29868.32979
|View full text |Cite
|
Sign up to set email alerts
|

Footprints in the cache

Abstract: This paper develops an analytical model for cache-reload transients and compares the model to observations based on several address traces. The cache-reload transient is the set of cache misses that occur when a process is reinitiated after being suspended temporarily. For example, an interrupt program that runs periodically experiences a reload transient at each initiation. The reload transient depends on the cache size and on the sizes of the footprints in the cache of the competing programs, where a program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 11 publications
0
40
0
1
Order By: Relevance
“…Thiébaut and Stone [19] modeled the amount of additional misses caused by context switches for set-associative caches. Agarwal, Horowitz and Hennessy [1] also included the effect of conflicts between processes in their analytical cache model and showed that inter-process conflicts are noticeable for a mid-range of cache sizes that are large enough to have a considerable number of conflicts but not large enough to hold all the working sets.…”
Section: Related Workmentioning
confidence: 99%
“…Thiébaut and Stone [19] modeled the amount of additional misses caused by context switches for set-associative caches. Agarwal, Horowitz and Hennessy [1] also included the effect of conflicts between processes in their analytical cache model and showed that inter-process conflicts are noticeable for a mid-range of cache sizes that are large enough to have a considerable number of conflicts but not large enough to hold all the working sets.…”
Section: Related Workmentioning
confidence: 99%
“…The union of the read-set and the write-set of a transaction is sometimes called the footprint [100] of the transaction, i.e., the set of data items that have be accessed within the transaction.…”
Section: General Transactional Memory Terminologymentioning
confidence: 99%
“…While many studies at that time argued that most transactions were small (short) and/or occurred infrequently, Ananian et al argued that a transactional memory system "should support transactions of arbitrary size and duration" [4]. In other words, the system shall be able to handle transactions with footprints, i.e., the set of memory locations accessed [100], almost as large as the size of the virtual memory of the system. Further, a transaction can also execute for an arbitrary long time.…”
Section: Transactional Lock Removal Tlrmentioning
confidence: 99%
“…Prior research [1,57] has investigated various analytic cache models by extracting parameters from the reference trace. Simulation techniques, such as cache profiling [43,39], can provide insight on potential program transformations by classifying misses according the cause of the cache miss.…”
Section: Related Workmentioning
confidence: 99%